Brand experience: a study on the experiences that influence the decision of the consumer purchase of Conceiçoense - BA between 2019 and 2020 - case Tambaú - Jesus , Gabriela dos Santos de; Brandão , Lôise da Cruz; Campos, Kézia Ferreira (Seven Editora, 2023)
The Brand experience is a marketing strategy, arising from interactions between the customer and the brand that generate experiences, which directly influence their purchase decision. The brand, in its entirety, needs to be focused on its consumers to provide meaningful experiences.  Therefore, it is essential to understand consumer behavior, which undergoes constant transitions that end up making it more and more meticulous.  As a result, the present study is based on bibliographical research, followed by a case study with a quantitative approach, which aimed to identify the experiences that influence the purchasing decision of the conceptual consumer.  To obtain the data, questionnaires were applied using the theory of simple random sampling in two different periods, 2019 and 2020. The results claim that the experiences that positively influence the purchase decision are focused on traditional values such as quality and honesty, in addition to a culture focused on satisfying customer needs. DOI:https://doi.org/10.56238/methofocusinterv1-044